MAGNETIC FLUIDS AND NANOCOMPOSITES: IMPROVING THE MAGNETIC RESPONSE - SOCOLIUC, V.; TURCU, R.; SUSAN-RESIGA, D.; BORBÁTH, T.; VÉKÁS, L. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Magnetic nanofluids, nano-micro composite fluids and polymeric nanocomposites designed for leakage-free rotating magnetofluidic seals and for biomedicine and magnetic separation are reviewed. The synthesis procedures and the magnetic and magnetorheological properties are discussed in terms of achieving the highest volume or mass magnetization of the nanomaterials prepared for specific applications.